Contrasting SARS-CoV-2 epidemics in Singapore: cohort studies in migrant workers and the general population. (February 2022) - Clapham, Hannah E; Chia, Wan Ni; Tan, Linda Wei Lin; Kumar, Vishakha; Lim, Jane M; Shankar, Nivedita; Tun, Zaw Myo; Zahari, Marina; Hsu, Li Yang; Sun, Louisa Jin; Wang, Lin Fa; Tam, Clarence C
Highlights: 64% of residents in a SARS-CoV-2-affected dormitory were infected by July 2020 < 0.2% of the Singapore general population were infected with SARS-CoV-2 in 2020 SARS-CoV-2 spread can be suppressed with prompt, wide-ranging interventions High-risk, crowded settings require special consideration in preparedness planning Lowering densities in these settings is key to reducing vulnerability to outbreaks Abstract: Importance: Since January 2020, Singapore has implemented comprehensive measures to suppress SARS-CoV-2. Despite this, the country has experienced contrasting epidemics, with limited transmission in the community and explosive outbreaks in migrant worker dormitories. Objective: To estimate SARS-CoV-2 infection incidence among migrant workers and the general population in Singapore. Design: Prospective serological cohort studies. Setting: Two cohort studies — in a migrant worker dormitory and in the general population in Singapore. Participants: 478 residents of a SARS-CoV-2-affected migrant worker dormitory were followed up between May and July 2020, with blood samples collected on recruitment and after 2 and 6 weeks. In addition, 937 community-dwelling adult Singapore residents, for whom pre-pandemic sera were available, were recruited. These individuals also provided a serum sample on recruitment in November/December 2020. Exposure: Exposure to SARS-CoV-2 in a densely populated migrant worker dormitory and in the general population. Main outcomes and measures: The main outcome measures were the incidences of SARS-CoV-2 infection in migrant workers and in the general population, as determined by the detection of neutralizing antibodies against SARS-CoV-2, and adjusting for assay sensitivity and specificity using a Bayesian modeling framework. Results: No evidence of community SARS-CoV-2 exposure was found in Singapore prior to September 2019. It was estimated that < 2 per 1000 adult residents in the community were infected with SARS-CoV-2 in 2020 (cumulative seroprevalence: 0.16%; 95% CrI: 0.008–0.72%). Comparison with comprehensive national case notification data suggested that around 1 in 4 infections in the general population were associated with symptoms. In contrast, in the migrant worker cohort, almost two-thirds had been infected by July 2020 (cumulative seroprevalence: 63.8%; 95% CrI: 57.9–70.3%); no symptoms were reported in almost all of these infections. Conclusions and relevance: Our findings demonstrate that SARS-CoV-2 suppression is possible with strict and rapid implementation of border restrictions, case isolation, contact tracing, quarantining, and social-distancing measures. However, the risk of large-scale epidemics in densely populated environments requires specific consideration in preparedness planning. Prioritization of these settings in vaccination strategies should minimize the risk of future resurgences and potential spillover of transmission to the wider community.